A controversy about historical relics. Dora Mayer and her controversial proposal in debate in the Lima press (1916) - Chipana Rivas, Jhonny (2022)
This article analyzes the traditional use of archaeological objects, as an appetizing treasure, during the Aristocratic Republic (1895-1919). This article takes as starting point a journalistic controversy produced in 1916, among average citizens, not specialized in the subject, initiated by a prominent member of the Pro-Indigenous Association. This debate proposes to legalize the extraction and export market of said objects, in favor of scientific expeditions that valued the role of indigenous people in pre-Hispanic culture, establishing an economic rate for the benefit of their direct heirs, the indigenous people. Different interests in play are described: between conservatives and liberals, nationals and foreigns actors, creole and indigenous. The possible scope and perspective of this proposal in the horizon of rights of the indigenous community are discussed as well.